Development and application of neurosurgery robots and navigation systems - DING Hui; WANG Guang⁃zhi (Chinese Journal of Contemporary Neurology and Neurosurgery)
The rapid development of neurosurgery robots and navigation systems has significantly enhanced surgical precision and safety. Neurosurgery robots, based on stereotactic technology, achieve submillimeter⁃level positioning through multi⁃modal image fusion and non⁃invasive registration techniques. Equipped with high⁃degree⁃of⁃freedom robotic arms and integrated sensors, they precisely perform complex procedures such as stereo⁃electroencephalography (SEEG) electrode implantation, deep brain stimulation (DBS) device placement, and magnetic resonance⁃guided laser interstitial thermal therapy (MRgLITT). Navigation systems employ optical or electromagnetic tracking technologies combined with multi⁃modal imaging to assist surgeons in tracking important structures and target lesion tissue precisely. Future advancements may autonomously generate personalized surgical plans to reduce human error, while flexible robotic arms and novel endoscope⁃holding robots could expand endoscopic applications. Furthermore, the integration of multiple technologies will broaden neurosurgical applications. These innovations not only minimize complication risks and shorten treatment periods, but also propel the field toward intelligent, minimally invasive neurosurgery.